PRARANCANGAN PENGOLAHAN LlMBAH RESIN BEKAS TANPA BAHAN MATRIKS DARI PLTN TIPE PWR 1000 MW - Cerdas Tarigan (Jurnal Perangkat Nuklir, 2010)
PRE DESIGN PROCESSING OF WASTE of EX-RESIN WITHOUT MATERIALS MATRIX FROM NUCLEAR POWER PLANT TYPE PWR 1000 MW Have been done pre design processing of waste ex-resin without capacities matrix materials from nuclear power plant type PWR 1000 MW During the time radioactive waste of ex-resin processed to use process of immobilization use matrix materials like mixture cement and epoxy resin and then conditioning. This process is not effective and efficient because end result volume of end product bigger than volume early operation system and maintenance of its installation more difficult. To overcome this created a design of technology processing of waste of ex- resin without matrix materials through process of strainer, drying and conditioning represent technological innovation newly processing of radioactive waste of ex-resin. Besides this process more effective and efficient, volume of end product waste much more small from volume early and operation system and maintenance of its easier installation. Pre design is expected to be used as a basis to make conceptual of pre design installation of strainer, drying and conditioning for the processing of waste of ex- resin from nuclear power plant type PWR 1000 MW   PRARANCANGAN PENGOLAHAN LlMBAH RESIN BEKAS TANPA BAHAN MA TRIKS DARI PL TN TlPE PWR 1000 MW Telah dilakukan prarancangan pengolahan limbah resin bekas tanpa bahan matriks dari PL TN tipe 1000 MW Selama ini limbah radioaktif resin bekas diolah menggunakan proses immobilisasi menggunakan bahan matriks seperti campuran semen dan resin epoksi kemudian dikondisioning. Proses ini kurang efektif dan efisien karena volume hasil akhir olahan lebih besar dari volume awal limbah dan sistem pengoperasian dan perawatan instalasinya lebih sulit. Untuk mengatasi hal ini dibuat suatu prarancangan teknologi pengolahan limbah resin tanpa bahan matriks melalui proses penirisan, pengeringan dan kondisioning merupakan inovasi teknologi baru pengolahan limbah radioaktif resin bekas. Selain proses ini lebih efektif dan efisien volume hasil akhir olahan jauh lebih kecil dari volume awal limbah dan sistem pengoperasian dan perawatan instalasinya lebih mudah. Prarancangan ini diharapkan dapat digunakan sebagai dasar untuk membuat konsepsual prarancangan instalasi penirisan, pengeringan dan kondisioning untuk pengolahan limbah resin bekas dari PL TN PWR 1000MW